Časný karcinom žaludku - Douda, Ladislav; Cyrany, Jiří; Tachecí, Ilja (Vnitrni lekarstvi, 2022)
Early gastric cancer is defined histopathologically as a tumour with limited local progression to the mucosa and submucosa. The concept of early cancer was developed in the 1960s in Japan and is now widely accepted. The term of early gastric cancer included cases with/without metastatic lymph node involvement. However, a common characteristic is a favourable prognosis of the disease. The task of the endoscopist is primarily to diagnose (identify) the tumour (precancerous lesions) and to verify it by biopsy. Successful identification must be followed by its correct classification, leading to the choice of an adequate approach, which includes surveillance, endoscopic treatment (resection) or surgical treatment (with or without chemotherapy). The method of treatment is determined primarily by the nature or risk of lymph node involvement.
Keywords: nádory žaludku; prognóza; lidé; lymfatické metastázy; Lymphatic Metastasis; gastroscopy; Gastric cancer; lymfatické uzliny; gastroskopie; Lymph Nodes; gastric cancer; Humans; Stomach Neoplasms; early cancer; Gastroscopy; endoscopic resection; Prognosis